TEACHER GUIDANCE IN THE IMPLEMENTATION OF CURRICULUM 2013 (K-13) FOR EARLY CHILDHOOD EDUCATION IN THE LANGKAT REGENCY - Marbun, Sariana; Simatupang, Dorlince (Universitas Negeri Medan, 2018)
Abstract The background of the study comes from the low ability of teachers in designing scientific-based learning implementation plan (RPPH) for the Scientific and Local Culture subject and carrying out the authentic assessment for early childhood education (PAUD) students. These activities aim to assist teachers developing Weekly Implementation Plan (RPPM) and RPPH on the aforementioned subject as well as to help teachers developing the authentic assessment instruments in measuring early child development outcomes. The activities were conducted in the Ananda Kindergarten and Early Childhood Education (School Partners) in the Sub-District of Gebang at the District of Langkat from July to September 2017. The participants were teachers in the Partner School and PAUD teachers around the School of Partners, amounting 20 teachers using discussion, questioning, group work and assignment as well as the monitoring and evaluation approaches. The results of the mentoring activities showed that: 1) Most teachers were able to develop RPPM and RPPH based on Scientific and Local Culture, and only a few teachers with senior secondary education background had difficulty in preparing the RPPH according to the guidelines; 2) Most teachers experienced difficulties in developing authentic assessment instruments, 3) Teachers of PAUD were enthusiast engaging in the mentoring activities validated by their presences and activities during processes. The results of these activities recommend that: 1) Do consistent and continuous monitoring of the implementation of learning in accordance with the lesson plans that have been prepared; 2) the need for special teacher assistance in the development of authentic assessment instruments for early childhood; 3) The need for special assistance in development and preparation of media and educational game tools in accordance with the needs of early childhood. Keywords: scientific-based learning implementation plan (RPPH), Scientific and Local Culture, early childhood education (PAUD) students, Weekly Implementation Plan (RPPM), District of Langkat